A promising hybrid graphite counter electrode doped with fumed silica nano-spacers for efficient quasi-solid state dye sensitized solar cells. (20th January 2018) - Mengal, Naveed; Arbab, Alvira Ayoub; Memon, Anam Ali; Sahito, Iftikhar Ali; Jeong, Sung Hoon
Abstract: Preparation of low-cost electrocatalytic counter electrode (CE) at low temperature is desired in the fabrication of photo-electrochemical quasi-solid state dye-sensitized solar cell (Qs-DSSC). We present facile doping of fumed silica (SiO2 ) as mesoporous nano-spacers in cationically functionalized graphite network and its synthesis into an electrically conductive hybrid paste for Qs-DSSC CEs. Polyethylene oxide (3%) based electrolyte solution is used as a quasi-solid gel electrolyte. With an optimized quantity of fumed silica nano-spacers (10%), an increase of 53.6% is achieved in power conversion efficiency (PCE) compared to bare cationised graphite coated CE. Our suggested Si@G 10% CE demonstrates commendable power conversion efficiency of 6.42% compared to 7.32% with expensive platinum (Pt) based Qs-DSSC. It exhibits a low charge transfer resistance (RCT ) of 0.61 Ω cm 2, owing to the improved interconnection, formation of the porous structure, and enhanced mobility of electrolyte ions. The cyclic voltammetry (CV) shows excellent electro-catalytic activity towards the I − / I 3 − redox couple and it is stable up to 50 cycles at a scan rate of 10 mV s −1 . The facile synthesis route, excellent electro-catalytic activity, appreciable stability, and considerable photovoltaic performance makes Si@G 10% based CE a promising candidate for Qs-DSSC fabrication. Graphical abstract: Image 1 Highlights: Facile synthesis of highly electro-catalytic silica doped graphite hybrid paste. Formation of porous structure at counter electrode for enhanced ions mobility. Low charge transfer resistance (RCT ) of 0.61 Ω cm 2 in Si@G based dummy cell. Commendable power conversion efficiency (PCE) of 6.42% in Qs-DSSC. Compared to graphite coated CE, a 53.6% enhancement in PCE was achieved.